Sengkarut kemiskinan masyarakat desa dalam novel Aib dan Nasib karya Minanto - Angesty, Chintya; Nurulhady, Eta Farmacelia; Waluyo, Sukarjo (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This research was carried out with the aim of analyzing (1) the structure of “Aib dan Nasib” with heuristic reding, (2) the village and its chaos in poverty according to Robert Chambers' view, and (3) the reasons why the village community experiences a chaotic life. This research was carried out using the literary sociology method with the help of the theory of poverty put forward by Robert Chambers and presented in a qualitative descriptive manner. This research is in the form of a literature study with the novel “Aib dan Nasib” as the main source or object of research. The results of this research prove that people in rural areas tend to experience poverty due to various factors such as proper poverty, helplessness, vulnerability in facing emergency situations, dependency, and alienation. People in villages also experience a messy life caused by the shackles of poverty that never escape. The tangled threads between events make their lives even more complicated because there is no way out that can be taken because of the limitations they have.